2007
DOI: 10.1002/chin.200735137
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Synthesis of Flavanones and Chromanones.

Abstract: Catalytic Enantioselective Synthesis of Flavanones and Chromanones. -Bifunctional thiourea catalysts (I) and (II) promote the asymmetric oxo-conjugate addition to a β-ketoester alkylidene in high yields and excellent enantioselectivity for aryl and alkyl substrates. Subsequent decarboxylation of the β-ketoester proceeds smoothly in a one-pot procedure. -(BIDDLE, M. M.; LIN, M.; SCHEIDT*, K. A.; J. Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Chiral thioureas derived from quinine/quinidine scaffolds have been adapted as synthetic mimetics of CHI enantioselective functionality. 39,40 The human gut bacterium, Eubacterium ramulus, which evolved CHI activity from an unrelated protein fold, reverses the reaction for flavonoid catabolism. 41,42 The bacterial CHI is similar to plant CHIs in its selectivity for (2S)flavanones; however, for the bacterial CHI, an active site histidine facilitates a general acid/base catalysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Chiral thioureas derived from quinine/quinidine scaffolds have been adapted as synthetic mimetics of CHI enantioselective functionality. 39,40 The human gut bacterium, Eubacterium ramulus, which evolved CHI activity from an unrelated protein fold, reverses the reaction for flavonoid catabolism. 41,42 The bacterial CHI is similar to plant CHIs in its selectivity for (2S)flavanones; however, for the bacterial CHI, an active site histidine facilitates a general acid/base catalysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Biddle et al recently reported the discovery of a bifunctional quinine-derived thiourea catalyst that effectively regulates the chemical outcome and produces either a lefthanded molecule or a right-handed molecule, not a one-to-one mixture of both. This catalyst was used in flavanones and chromanones synthesis and high yields were reported with excellent enantioselectivity, in addition to the advantages of further modification capability [20]. Apart from chemical synthesis, different polyphenols biosynthesis approaches with each offers advantages and disadvantages are available, for example plant extract, plant cell cultures, and recombinant microororganisms.…”
Section: Biosynthesis Methodsmentioning
confidence: 99%
“…319 Other catalysts have been used to perform the intramolecular oxa-Michael cyclization, and we discuss now the reaction with chiral 9-(benzyloxy)cinchonidine thiourea (3R,8S,9R)-CXLVII. 320 The reaction was first optimized on tert-butyl 3-(2-hydroxyphenyl)-3-oxo-2-benzylidenepropanoate (E)-657, which afforded tert-butyl 3,4-dihydro-4-oxo-2-phenyl-2H-chromene-3-carboxylate [(2R,3S)-658] through an oxa-Michael attack on the β-Re face and the sequential syn addition. Then the reaction was run under the conditions that led to the decarboxylation product (R)-659 (Scheme 271).…”
Section: Formation Of the O(1)−c(2) Bondmentioning
confidence: 99%
“…Then the reaction was run under the conditions that led to the decarboxylation product (R)-659 (Scheme 271). 320 Considering the structure of the cinchona fragment of the catalyst and the stereochemical outcome, the reader will certainly be surprised by the analogies of this reaction with the reaction described in Scheme 270 from (Z)-652 to (8S,9S)-653.…”
Section: Formation Of the O(1)−c(2) Bondmentioning
confidence: 99%